The Development of the Turkish Social Media Craving Scale (SMCS): a Validation Study - Savci, Mustafa; Griffiths, Mark D. (Springer, 2021)
Over the past decade, the use of social media applications have increased worldwide. In parallel with this, abuse of social media has also increased. In recent years, many disorders related to social media use have been conceptualized. One of the common consequences of these disorders is the intense desire (i.e., craving) to use social media. The aim of the present study was to develop the Social Media Craving Scale (SMCS) by adapting the Penn Alcohol Craving Scale (PACS). The study comprised 423 university students (242 females and 181 males) across five different samples. The psychometric instruments used included the Social Media Craving Scale, Social Media Disorder Scale, Brief Self-Control Scale, and Personal Information Form. In the present study, structural validity and reliability of the SMCS were investigated. The structural validity of SMCS was investigated with Exploratory Factor Analysis (EFA), confirmatory factor analysis (CFA), and criterion validity. The reliability of SMCS was evaluated using Cronbach alpha internal consistency reliability coefficient, corrected item total correlation coefficients, and test-retest method. As a result of EFA, the SMCS was found to be unidimensional scale. This unidimensional structure explained approximately half of the total variance. The unidimensional structure of SMCS was tested in two different samples with CFA. As a result of CFA, SMCS models were found to have acceptable fit values. The criterion validity of the SMCS was evaluated by assessing social media disorder, self-discipline, impulsiveness, daily social media use duration, social media usage history, frequency of checking social media accounts during the day, number of social media accounts, and number of daily shares. Analysis demonstrated that the SMCS was associated with all these variables in the expected direction. According to the reliability analysis (Cronbach's alpha internal consistency coefficients, corrected item total correlation coefficients, and test-retest method), the SMCS was found to be a reliable scale. When validity and reliability analyses of the SMCS are considered as a whole, it is concluded that the SMCS is a valid and reliable scale in assessing social media craving.
Keywords: Social media; Social media addiction; Craving; Social media craving; Social Media Craving Scale